1999
DOI: 10.1097/00006123-199906000-00115
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxy for Hypothalamic Hamartoma with Intractable Gelastic Seizures: Technical Case Report

Abstract: OBJECTIVE AND CLINICAL IMPORTANCE: We report a patient with a hypothalamic hamartoma treated by stereotactic radiofrequency thermocoagulation. CLINICAL PRESENTATION: A 15-year-old girl presented with a hypothalamic hamartoma associated with intractable gelastic and tonic seizures. There were no clinical signs of precocious puberty. Magnetic resonance imaging revealed an isointense suprasellar mass, about 1 cm in diameter. TECHNIQUE: A depth electrode was placed into the hamartoma using a computed tomography-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 11 publications
0
34
0
2
Order By: Relevance
“…In conjunction with the evolution of the surgery for HH was the increasing application of stereotactic radiosurgery. 28 Further treatment options for HH are radiofrequency lesioning 15,19 and interstitial radiotherapy with 125 I, 32,34 but the sample sizes reported are smaller and these treatments are not freely available.…”
Section: The Development Of Surgery For Hhmentioning
confidence: 99%
“…In conjunction with the evolution of the surgery for HH was the increasing application of stereotactic radiosurgery. 28 Further treatment options for HH are radiofrequency lesioning 15,19 and interstitial radiotherapy with 125 I, 32,34 but the sample sizes reported are smaller and these treatments are not freely available.…”
Section: The Development Of Surgery For Hhmentioning
confidence: 99%
“…9,13,24,35,37,44,45 Substantial seizure improvement following resection, disconnection, or ablation is further proof of the intrinsic epileptogenesis of HHs and the need for a direct approach to produce seizure relief. [2][3][4]8,9,[12][13][14][16][17][18]24,25,28,35,36,[44][45][46][47][48]51,52 The degree of seizure control is linked to the extent of the surgical intervention. Incomplete resection, disconnection, or ablation of the HH can be associated with incomplete seizure control, whereas freedom from seizures may be induced by a more aggressive approach.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…8 Radiofrequency ablation has also been described. 17,18,25,36 Surgical morbidity is limited overall, especially considering the challenging neural and vascular anatomy surrounding the HH, but includes thalamocapsular infarcts with resulting hemiparesis or hemiplegia, oculomotor palsy, visual field deficits, short-term memory deterioration, hyperphagia, hypothyroidism, and diabetes insipidus. 14,35,44 Complete seizure freedom is difficult to achieve, but in most cases remarkable long-term improvements have been reported with near-total resolution of disabling seizure types and enhanced cognitive and psychosocial abilities.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…4,17) The epilepsy is frequently refractory to antiepileptic drugs. Depth electrode recordings have demonstrated that gelastic seizures arise within the hamartoma, 1,3,5,7,11,13) so resection of the hamartoma seems to be the most appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various therapeutic approaches for epilepsy have been attempted with encouraging results, including gamma knife surgery, 2,18,22) radiofrequency thermocoagulation, 7) and chronic electrical stimulation of the hamartoma and microsurgery using different routes. 14,15,20,23) Most previous studies have included single cases or series, some of precocious puberty only, others with epilepsy only or both.…”
Section: Introductionmentioning
confidence: 99%